Enhancing student creativity through online learning: A study of SPADA Indonesia in Civic Education courses at Universitas Pendidikan Indonesia and Universitas Lambung Mangkurat - Iswandi, Dede; Budimansyah, Dasim; Komalasari, Kokom; Fitriasari, Susan (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This study examines the effectiveness of the SPADA Indonesia online learning platform in fostering creativity among students enrolled in Civic Education courses at Universitas Pendidikan Indonesia (UPI) and Universitas Lambung Mangkurat (ULM) Banjarmasin. Given the increasing importance of creativity as a critical skill for future graduates, this research aims to explore how the features and interactive elements of SPADA Indonesia contribute to enhancing student creativity within the context of mandatory Civic Education curricula. A total of 90 students participated in this study, comprising 45 from each university, selected through purposive sampling to ensure a diverse representation of experiences and perspectives. Data collection involved pre- and post-intervention surveys, focus group discussions, and observational analysis of student activities within the online platform. The findings reveal that students reported increased engagement, flexibility, and creative problem-solving skills when using SPADA Indonesia for their coursework. Furthermore, the study identifies specific platform aspects"”such as interactive modules, collaborative forums, and multimedia resources"”that positively impact students' creative capacities. The results suggest that SPADA Indonesia can be a valuable tool in enhancing creativity within Civic Education, with implications for its integration into broader academic curricula. These findings significantly impact the wider scholarly community, potentially shaping the future of education. Recommendations for optimizing the use of online learning platforms to support creative development were discussed.